Clinical outcomes of risk-based caries prevention in preschool-aged children - Pienihäkkinen K, Jokela J: (Blackwell Synergy, 2002)
The aim of this study was to evaluate outcomes in young children of risk-based management of dental caries in comparison with routine prevention.